Du Moyen-Âge barbare au Moyen-Âge matrice de la modernité : histoire d’une métamorphose historiographique. Du romantisme à l’histoire des mentalités 1830-2015. - Christian Amalvi (Perspectives Médiévales)
In the romantic period, the Middle Ages represents both a picturesque and a frightful time. Picturesque because of the Cour des miracles, the Feast of Fools and the Carnival. However the power of the Church on society frightens the liberals and the republicans. Yet, one hundred and fifty years later, the works of the historians of the Annales School – Georges Duby, Jacques Le Goff, Emmanuel Le Roy Ladurie, Jean Favier – present a much more positive face of the medieval period. The present article tries to explain the shift from a terrifying Middle Ages to a Middle Ages in full light, symbolized by its wonderful artistic creations, in particular Gothic cathedrals.